Engaging Men to Transform Gender Attitudes and Prevent Intimate-Partner Violence in the Democratic Republic of Congo - Falb, Kathryn; Hossain, Mazeda; Kabeya, Rocky; Koussoube, Estelle; Lake, Milli; Lewis, Chloe; Pierotti, Rachael S.; Roth, Danielle; Vaillant, Julia (World Bank, Washington, DC, 2021)
Over a third of women in the Democratic Republic of Congo (DRC) have experienced physical or sexual intimate-partner violence (IPV) in the past year (2013-2014 DHS). In this context, the Africa Gender Innovation Lab (GIL) in collaboration with the International Rescue Committee (IRC) tested the effectiveness of the Engaging Men through Accountable Practice (EMAP) program. EMAP is a male-only discussion group intervention aimed to prevent IPV, and to transform gender attitudes and couples’ power dynamics; all male discussion groups are informed by and accountable to women’s groups in the community. The EMAP program significantly improved the quality of the couple relationships and led to changes in men’s behaviors that are often associated with IPV, like reduced alcohol consumption. Further, the study found that the discussion groups led to improvements in men’s gender equitable attitudes, reducing their support for violence against women and increasing their support for a woman’s right to refuse to have sex. Despite these changes on the journey to IPV prevention, female partners of male EMAP participants reported, on average, no change in the levels of IPV that they experienced.